1999
DOI: 10.1089/end.1999.13.539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mobile Lithotripters at One Institution: Healthtronics LithotronTM, Dornier MFL-5000, and Dornier Doli

Abstract: Statistically equivalent success rates were achieved with all three machines. The electromagnetic unit (Doli) had higher rates of retreatment and significant complications than the electrohydraulic lithotripters (MFL-5000, Lithotron).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…These factors may result in significant differences in the potential clinical efficacy 2,60 . Comparison studies with lithotriptors (for renal stones only) have described the electrohydraulic method as being more clinically effective in stone fragmentation compared with electromagnetic or piezoelectric devices 66 . The machine used for the current musculoskeletal studies employed electrohydraulic shock-wave generation and was the first shock-wave device approved by the Food and Drug Administration for any musculoskeletal indications 53 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors may result in significant differences in the potential clinical efficacy 2,60 . Comparison studies with lithotriptors (for renal stones only) have described the electrohydraulic method as being more clinically effective in stone fragmentation compared with electromagnetic or piezoelectric devices 66 . The machine used for the current musculoskeletal studies employed electrohydraulic shock-wave generation and was the first shock-wave device approved by the Food and Drug Administration for any musculoskeletal indications 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Fuselier et al [3] reported similar results for intravenous sedation (68%) with the Doli 50 lithotriptor.…”
Section: Discussionmentioning
confidence: 69%
“…Various lithotriptors are currently available for shockwave lithotripsy, with the chief differences being the energy source and size of the focal point [2]. Intramuscular sedation [4], topical agents [5], analgesia pump [6], spinal anesthesia [7], general anesthesia [8], and monitored anesthesia care with intravenous sedation [3] are the variety of anesthesia techniques used for ESWL. The choice of anesthesia varies with the institution, physician and/or patient preference, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate was 68% for the electromagnetic unit versus 72-80% for the electrohydraulic units. However, higher retreatment and complication rates were reported with the Doli unit [4].…”
Section: Discussionmentioning
confidence: 91%